MODERN EPILEPTOLOGY. PROBLEMS AND SOLUTIONS - G. N. Avakyan (Эпилепсия и пароксизмальные состояния)
Abstract: the primary tasks of the current stage in the therapy of epilepsies and epileptic syndromes are: the widespread introduction of new antiepileptic drugs with innovative mechanisms of action on the "target" pathological epileptic systems; the use of new AEDs, not only as additional therapy of drug-resistant epilepsies, but possibly more rapid transition to new forms of drugs at the early stages of ineffective treatment baseline probes.